Transposon sequencing: A powerful tool for the functional genomic study of food-borne pathogens. (December 2021) - Liu, Xiayu; Liu, Guangyu; Wu, Yansha; Pang, Xinxin; Wu, Yajing; Qinshu,; Niu, Jianrui; Chen, Qihe; Zhang, Xinglin
Abstract: Background: Genome-wide functional genetic studies of food-borne pathogens could provide a comprehensive understanding of the mechanisms underline their survival and pathogenesis in the harsh environments during food processing and infections. Traditional methods such as physical mutagenesis, chemical mutagenesis, and labeled DNA fragment insertion mutation techniques are time-consuming, labor-intensive and low precision. Although RNA-Seq and other omics methods enable high-throughput research on a genome-wide scale, the obtained results of gene transcription or expression cannot establish direct causal connection between the genetic determinants and particular functions. Scope and approach: Transposon sequencing (Tn-seq) is an emerging microbial functional genomic technology based on transposon mutagenesis and high-throughput sequencing technologies, which is able to quantitatively track millions of independent mutants in a single experiment, and therefore efficiently map the "genotype-phenotype" relationship and the genetic interaction networks of a bacterium. Key findings and conclusions: This article summarizes the common types and hazards of food-borne pathogens, the development of Tn-seq technology, and its applications in studying the physiology, pathogenesis, and environmental survival of food-borne pathogens. Highlights: Food-borne pathogens are a common concern of food safety worldwide. Transposon sequencing (Tn-seq) is an emerging microbial functional genomics technology. Tn-seq can efficiently establish "genotype-phenotype" correspondence. The development and applications of Tn-seq are reviewed.